Dementia and Impairment, Directions for no specialist physicians - Archibaldo Donoso (CAEN, 2007)
Alzheimer's disease (AD), that develops with progressive loss of cognitive functions, beginning by memory, is the most important Central Nervous System (CNS) degenerative affection and one of the main causes of invalidity in adults. The mild cognitive impairment (MCI) is defined as a discreet loss of memory and sometimes others abilities. In this case, the affected is not limited in their quotidian activities, meaning that dementia does not exist. However, it is very possible that in the following years the AD becomes evident.In the present review, some basics concepts about dementia are revised; etiologic classification, clinical manifestation and treatment, emphasizing the support that the patients and their families need.